Challenges for women's participation in communal forests: Experience from Nicaragua's in digenous territories - Evans, K.; Flores, S.; Larson, A.M.; Marchena, R.; Müller, P.; Pikitle, A. (Elsevier, 2017)
This paper analyzes sex-differentiated use, decision-making and perceptions regarding communal forests in indigenous communities of Nicaragua's Atlantic coast. Methods include a survey, focus groups, participant observation and adaptive collaborative management processes over a two-year period. Results revealed that while a higher percentage of men than women participate in the harvest of eight forest products, women participate substantially in product sales and have some control over income. A majority of men and women believe that women participate in decision-making, but that participation was of low efficacy. Women face significant obstacles to effective participation in forest decision-making in the community: weak community organization, pressure by spouses, difficulty organizing among themselves and informal sanctions. Improving meaningful participation of women in decision-making requires addressing challenges and obstacles at multiple levels; obstacles at the communal level, where the future of the forests will be decided, cannot be overcome without attention to the household.